THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY TOWARDS BRAND IMAGE AND CORPORATE REPUTATION ON THE STUDY OF THE BODY SHOP "FOREVER AGAINTS ANIMAL TESTING" CAMPAIGN - Warsita, Meisy; Indriastuti, Herning (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research aims to discover the influence of Corporate Social Responsibility (CSR) towards Corporate Reputation which Mediated by Brand Image on The Body Shop “Forever Against Animal Testing” Campaign. The data used in this research is primary data obtained from the result of respondent given to 126 respondents by using purposive sampling technique. The analysis method used is Structural Equation Model (SEM) analysis with AMOS analysis tool and Sobel Test. The result of this research shown that there is positively significant influence of Corporate Social Responsibility (CSR) towards brand image, there is no a significant influence of Corporate Social Responsibility (CSR) towards corporate reputation, there is a positively significant influence of Brand Image towards Corporate Reputation, there is a positively significant influence of Corporate Social Responsibility (CSR) towards corporate reputation which mediated by Brand Image on The Body Shop “Forever Against Animal Testing” Campaign.